The Relationship Between the Level of Academic Performance in a Foreign Language and Some Psychological Characteristics of Students - Abzaletdinova, Alisa Ranisovna; Sorokoumova, Galina Veniaminovna (Razvitie obrazovaniâ (Online), 2022)
The article analyzes some psychological characteristics of students that are associated with the success of mastering a foreign language. The article presents the results of a study of the relationship between academic performance in a foreign language and cognitive functions (memory), motivation, and communicative abilities of students in grades 5–7. Introduction. The article examines the external and internal factors that are associated with the success of mastering a foreign language. Summarizing various approaches, the authors identified cognitive, motivational and communicative features of students that affect the success of mastering a foreign language, one of the indicators of which is the level of academic performance. Materials and methods of research. To study the relationship between academic performance in a foreign language and individual characteristics of students: memory, motivation, communicative abilities, the article presents the results of the study. To study the psychological characteristics of students in grades 5–7, the authors used the following psychodiagnostic techniques: «Memorization of 10 words» (A.R. Luria), «Methods for studying the motivation of the teaching of adolescents» (M.I. Lukyanova, N.V. Kalinina), «Communicative and organizational inclinations (KOS)" (V.V. Sinyavsky, V.A. Fedoroshin). Results and their discussion. The results of the study showed the relationship of academic performance in a foreign language with the level of auditory memory, with internal motivation to learn a foreign language and with the communicative abilities of students. Conclusions. The article concludes that it is necessary for teachers to use game technologies in foreign language lessons for the formation of auditory memory, active teaching methods, elements of psychological and communicative trainings, IT technologies for the development of internal motivation to learn a foreign language and communicative inclinations and abilities of students.